The Frightened Ones by Dima Wannous. The Study of Trauma between the Demonstration of Discourse and Narrative Structure - Abu Shehab, Rami (Dirasat: Human and Social Sciences, 2024)
Objectives: This research aims, in part, to provide a theoretical framework for what is known as Truama literature in light of the repercussions of political events and their impact. It also seeks to analyse Truama within the narrative model by identifying discursive representation at the level of structures employed by the narrative, specifically in the novel The Frightened Ones by Syrian novelist Dima Wannous. This includes examining the narrative effectiveness in light of representations of trauma and the contexts they achieve, alongside the accompanying themes, in order to test the hypothesis of the correlation between truama and narrative structure and its transformations. Methods: The research adopts an analytical approach based on the theory of trauma criticism and its literature, drawing from the theories of Cathy Caruth, in addition to the intersection of this approach with postcolonial theory, cultural criticism, feminism, and psychoanalysis. Results: The research yields several results that were determined by monitoring the representation of truama according to the semantic configuration, which is represented by the prevalence of models of psychological disorders resulting from the recall of traumatic events. These events include torture, displacement, and murder, in addition to childhood memories, within narrative frameworks and specific structures. Conclusions: The research concludes that representations of trauma are formed within specific frameworks, including the pattern of compensation and the parallel or binary formation of character consciousness. The dominance of the theme of fear is observed, in addition to the impact of trauma on the narrative structure in terms of the intentional prevalence of disorder at the structural level, as well as the effect of trauma on time and place. The role of memory in all of the aforementioned aspects is also emphasized.